2004
DOI: 10.1016/j.jvs.2003.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenting: is there a need to revise ultrasound velocity criteria?

Abstract: Currently accepted US velocity criteria validated in our laboratory for nonstented ICAs falsely classified several stented ICAs with normal diameter on carotid angiograms as having residual in-stent stenosis 20% or greater. We propose a new criterion that defines PSV less than 150 cm/s, with ICA/CCA ratio less than 2.16, as the best correlate to a normal lumen (0%-19% stenosis) in the recently stented ICA. This was associated with increased stiffness of the stented ICA (increased Ep, decreased Cp). These preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
144
0
12

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(159 citation statements)
references
References 30 publications
3
144
0
12
Order By: Relevance
“…However, ultrasonography might lead to an overestimation of ISR owing to an elevated velocity measurement from an increased stiffness of the vessel by the stent rather than a stenosis. 32 We remedied this limitation by arranging computed tomography/MR angiogram in suspected cases, and definitely, DSA in symptomatic patients with ISR.…”
mentioning
confidence: 99%
“…However, ultrasonography might lead to an overestimation of ISR owing to an elevated velocity measurement from an increased stiffness of the vessel by the stent rather than a stenosis. 32 We remedied this limitation by arranging computed tomography/MR angiogram in suspected cases, and definitely, DSA in symptomatic patients with ISR.…”
mentioning
confidence: 99%
“…Typical postprocedural carotid duplex sonographic velocities after successful stenting have been defined. Lal et al 3 proposed a PSV threshold of 150 cm/s or higher and a PSV ratio of 2.1 or higher for detecting residual poststent stenosis of 20% or greater; Setacci et al 12 proposed using a PSV threshold of higher than 105 cm/s for detecting poststent stenosis of 30% or greater, and AbuRahma et al 14 proposed a PSV of higher than 154 cm/s to define poststent stenosis of greater than 30%. We report reference ranges for carotid duplex sonographic velocities indicative of less than 20% stenosis on completion angiography that are consistent with these previously published criteria and confirm the observation that angiographically normal stented carotid arteries may have elevated sonographic velocities compared with native carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Carotid duplex sonography is the standard diagnostic test used for surveillance after carotid artery revascularization procedures, including carotid endarterectomy and carotid artery stenting. Several studies have shown elevated sonographic velocities after stenting in the absence of angiographically proven restenosis, [3][4][5][6] and whereas there have been several proposed distinct velocity-based diagnostic criteria for in-stent restenosis after stenting, 3,4,[6][7][8][9][10][11][12][13][14] most velocity criteria were developed shortly after stent placement. Few studies have explored whether Doppler flow T Article includes CME test velocities within successfully stented carotid arteries vary over time, thereby necessitating separate velocity criteria depending on the time from stent placement, or whether there are identifiable factors that influence poststent velocities.…”
mentioning
confidence: 99%
“…Dupplex ultrasound is commonly used to monitor restenosis in patients following CEA. Several authors in literature begin to report their experience in the use of ultrasonography as a follow-up tool in CAS too (Lal et al, 2004).…”
Section: Intra-operative and Post-operative Ultrasoundmentioning
confidence: 99%